New syllabus primary mathematics workbook 5B - Yee, Dr. Foong Pui (Karachi: Oxford University Press., 2024)
New Syllabus Primary Mathematics Workbook 5B complements the second half of the Primary Mathematics 5 textbook, focusing on key topics such as percentages, ratios, measurement, geometry, and introductory algebra. The workbook offers a variety of exercises designed to reinforce students' understanding and problem-solving skills. Each activity encourages independent learning and the practical application of mathematical concepts in real-world scenarios. By providing structured practice, the workbook helps students solidify their knowledge and prepares them for more advanced mathematical challenges, fostering confidence and competence in handling complex topics.